Practices and activities among healthcare personnel with severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection working in different healthcare settings—ten Emerging Infections Program sites, April–November 2020. (2nd August 2022) - Chea, Nora; Eure, Taniece; Penna, Austin R.; Brown, Cedric J.; Nadle, Joelle; Godine, Deborah; Frank, Linda; Czaja, Christopher A.; Johnston, Helen; Barter, Devra; Miller, Betsy Feighner; Angell, Katie; et al.
Abstract: Healthcare personnel with severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection were interviewed to describe activities and practices in and outside the workplace. Among 2, 625 healthcare personnel, workplace-related factors that may increase infection risk were more common among nursing-home personnel than hospital personnel, whereas selected factors outside the workplace were more common among hospital personnel.